Age-Related Changes in Gut Health and Behavioral Biomarkers in a Beagle Dog Population - Anna Fernández-Pinteño; Rachel Pilla; Jan Suchodolski; Emmanuelle Apper; Celina Torre; Anna Salas-Mani; Xavier Manteca (Animals)
The gut and the gut microbiome communicate with the nervous system through the gut–brain axis via neuroimmune and neuroendocrine mechanisms. Despite existing research, studies exploring this link in aging dogs are limited. This study aims to examine multiple blood and fecal biomarkers of intestinal health, along with various behavioral indicators based on saliva, blood, observations, and activity, in different age populations (junior: <2 y.o.; adult: 2–7 y.o.; senior: >7 y.o.) of thirty-seven Beagle dogs. In our study, Bacteroides were significantly higher in senior dogs. The relative abundance of Faecalibacterium and Blautia showed age-related trends, higher in senior and junior dogs, respectively. Fecal short-chain fatty acid concentration, especially acetate, increased with age, while propionate was higher in junior dogs. For the behavioral indicators we considered, blood thyroxine concentration, playing, exploring, and total activity were higher in junior dogs. The differences observed between the biomarkers of gut health and behavior, particularly those significant for the age correlations, emphasize the importance of considering age-related factors when studying the gut microbiome and behavior. However, further research is needed to better understand the mechanisms and specific pathways involved in the relationship between the studied biomarkers and age.